Pengendalian Pelaksanaan Pelayanan Nikah Pada Masa Pandemi Covid-19 : (Studi Pada Kanwil Provinsi Jambi) - Darmawan Ratdya Bakti; Shiddiq Sugiono (Jurnal Bimas Islam, 2021)
During the Covid-19 pandemic, the government issued various policies aimed at reducing the human crowd in socializing / social distancing. Even during a pandemic, the government must continue to carry out marriage services because this is a basic right of every citizen. In this case, the Director General of Islamic Guidance and Guidance at the Ministry of Religion also gave an appeal to exercise control over marriage services to all Religious Affairs Offices in Indonesia. The Jambi Provincial Regional Office in this case is one of the parties that has participated in carrying out this mandate. This study aims to provide an overview and analyze the implementation of control of the implementation of marriage services during the Covid-19 pandemic in Jambi Province. The method used in this research is descriptive analysis with a qualitative approach in analyzing the implementation of marriage service control policies at the Regional Office of the Ministry of Religion of Jambi Province. Based on the results of the study, in general there was a decrease in the number of marriages in Jambi Province during the Covid-19 pandemic. As for the results of the interview, the Regional Office has carried out various strategies such as being strict with the rules, working with relevant stakeholders and communicating intensely about health protocols. In addition, there are obstacles both from the negligence of the prospective bride and groom and the culture of the people themselves which tend to create cluster. Future research is expected to be able to evaluate more deeply the perspective of the community regarding the marriage program at the KUA during the Covid-19 pandemic.